Evaluation of the DynaTrap Flylight (DT-3009) Against House Flies and Stable Flies (Diptera: Muscidae) Under Indoor Conditions. Issue 6 (29th November 2019) - Hogsette, Jerome A; Cilek, James E
Abstract: Ultraviolet light traps are commonly used to manage house flies in indoor situations. Many indoor traps are longer than their 46-cm fluorescent tubes and have glue boards to capture attracted flies. Smaller traps have been sold to use in homes and small rooms, but few if any trap evaluations can be found in the literature. One trap, the DynaTrap Flylight DT-3009 (DTFL) has become quite common and a performance evaluation between it and an open-front commercial trap seemed warranted. Evaluations were conducted at the USDA-ARS-CMAVE laboratory in Gainesville, FL. The DTFL and the Gardner GT-200 open-front trap were evaluated individually and then in pairs. Traps were placed approximately 90 cm above the floor at the edge of a 2.4- × 0.76-m wide counter. Traps tested individually were centered on the long axis of the counter. For paired tests, traps were placed approximately 2.1 m apart. Fifty mixed-sex, 3- to 5-d-old house or stable flies were released and counts of captured flies were made after 1, 4, and 24 h. In individual tests, the DTFL and the GT-200 captured 38 and 76% of the house flies, respectively, and 3 and 18% of the stable flies, respectively, after 4 h. At 4 h in paired tests, the DTFL and the GT-200 captured 3 and 66% of the house flies, respectively, and 2 and 16% of the stable flies, respectively. Depending on the intended use, either trap was considered efficacious in capturing house flies when used alone. Differences in trap performance are discussed.